Strength of Brand Image and Restaurant Atmosphere in Influencing Decision Making and Customer Satisfaction - Aswin Juniarto; Tatik Suryani (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2023)
The purpose of this research is to analyze the strength of brand image and store atmosphere in influencing consumer decision making and satisfaction. The research was conducted using a quantitative approach with a questionnaire as a research instrument. The samples in this study were 105 customers at the Aiola Eatery Surabaya restaurant. Using the Partial Least Square (PLS) data analysis technique, the results show that both brand image and store atmosphere are proven to influence decision making and consumer satisfaction. The implication is that it is important for restaurant management to develop a brand image and create a comfortable atmosphere that can influence consumers to make buying decisions and be satisfied with the services provided.